2001
DOI: 10.1111/1475-679x.00027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence About Auditor–Client Management Negotiation Concerning Client’s Financial Reporting

Abstract: We develop a model of auditor‐client accounting negotiation, using the elements of negotiation examined in the behavioral negotiation literature, elaborated to include accounting contextual features indicated in the accounting literature and suggested by interviews with senior practitioners. We use a questionnaire structured according to the model to describe the elements, contextual features and associations between the two groups in a sample of real negotiations chosen by 93 experienced audit partners. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
278
2
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(303 citation statements)
references
References 38 publications
8
278
2
7
Order By: Relevance
“…Respondents are APs (Beattie, et al, 2000 and in the UK; Gibbins et al, 2001 in Canada), CFOs (Beattie, et al, 2000 and in the UK; Gibbins et al, 2005 and2007 in Canada) and, most recently, ACCs (Beattie, et al, 2008b in the UK). These studies have revealed substantial consistency in the responses of these groups.…”
Section: Audit Interaction Research and The Involvement Of The Audit mentioning
confidence: 99%
“…Respondents are APs (Beattie, et al, 2000 and in the UK; Gibbins et al, 2001 in Canada), CFOs (Beattie, et al, 2000 and in the UK; Gibbins et al, 2005 and2007 in Canada) and, most recently, ACCs (Beattie, et al, 2008b in the UK). These studies have revealed substantial consistency in the responses of these groups.…”
Section: Audit Interaction Research and The Involvement Of The Audit mentioning
confidence: 99%
“…Accountability theory suggests that when management is the auditor's client, there is a risk that auditors will unconsciously adopt the preferences of the management (Bazerman et al, 1997), because the antecedents for the acceptability heuristic are fulfilled: management acting as the client represents an important other party for the auditor; auditors have to justify their audit judgments and decisions to management (Gibbins et al, 2001;Sanchez et al, 2007); and auditors know management's preferred accounting method from the preliminary financial statements. Bamber and Iyer (2007) study accountability in a field-based analysis, and find that auditors who identify more strongly with management are more likely to acquiesce to the client-preferred treatment norms.…”
Section: Accountability Pressure and Client Typementioning
confidence: 99%
“…The first case covered the measurement of provisions for warranties and the second case covered allowances for bad debt. These accounting issues have often been considered in previous auditing research and are relevant to auditor-client meetings, since they affect reported earnings (Gibbins et al, 2001). We designed the cases to be ambiguous, since prior research suggests that auditors' independence is most strongly affected by client retention incentives (Hackenbrack and Nelson, 1996;Salterio and Koonce, 1997) and accountability pressure (Boiney et al, 1997) when no clear guidelines exist.…”
Section: Task and Dependent Variablesmentioning
confidence: 99%
“…According to the client-auditor negotiation literature, negotiations often result in less conservative reporting as auditors make compromises (Antle and Nalebuff, 1991;Gibbins et al, 2001). As a consequence, the problems in the accounts may not be eliminated after negotiation.…”
Section: Determinants and Implications Of Audit Reporting Lags In Chimentioning
confidence: 99%
“…According to Gibbins et al (2001), management views the negotiation as a win-lose situation and intend to persuade the auditors. Auditor's acquiescence or compromise is often expected.…”
Section: Audit Reporting Lag and Adverse Outcomesmentioning
confidence: 99%